2022
DOI: 10.1172/jci161408
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine synthetase limits β-catenin–mutated liver cancer growth by maintaining nitrogen homeostasis and suppressing mTORC1

Abstract: Glutamine synthetase (GS) catalyzes de novo synthesis of glutamine that facilitates cancer cell growth. In the liver, GS functions next to the urea cycle to remove ammonia waste. As dysregulated urea cycle is implicated in cancer development, the impact of GS' ammonia clearance function has not been explored in cancer. Here we show that, oncogenic activation of β-catenin led to decreased urea cycle and elevated ammonia waste burden. While β-catenin induced the expression of GS, which is thought to be cancer-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…[12,14,22] In various cancers, metabolic profile changes dramatically, and the phosphatidylinositol 3-kinase (PI3K)/ AKT/mTOR pathway is highly responsive to these changes, promoting the translation of MYC. [23][24][25][26] Therefore, the different expression patterns of ABCE1 in cancers might be related with these upstream factors.…”
Section: Discussionmentioning
confidence: 99%
“…[12,14,22] In various cancers, metabolic profile changes dramatically, and the phosphatidylinositol 3-kinase (PI3K)/ AKT/mTOR pathway is highly responsive to these changes, promoting the translation of MYC. [23][24][25][26] Therefore, the different expression patterns of ABCE1 in cancers might be related with these upstream factors.…”
Section: Discussionmentioning
confidence: 99%
“…recently provided evidence of GS’s tumour suppressor role in β-catenin-activated HCCs. 109 The authors used an in vivo approach in mice similar to that described above. They delivered c-Met and the constitutively active mutant of β-catenin (ΔN90-β-catenin) into livers, either wild-type or harbouring hepatocyte-specific ablation of GS (GS KO ).…”
Section: Is Glutamine Metabolism Pro-oncogenic or Tumour Suppressive ...mentioning
confidence: 99%
“…The impact of Wnt/β-catenin-induced metabolic changes on liver carcinogenesis has recently been thoroughly explored. [18][19][20] Other pathways have also been implicated in liver zonation mostly by counteracting Wnt/β-catenin signaling. Hedgehog signaling, although presenting low activity in healthy mature hepatocytes, is higher in the periportal region and hypothetically implicated in the regulation of zone 1 hepatocytes.…”
Section: Molecular Determinants Of Liver Zonationmentioning
confidence: 99%
“…More importantly, compelling studies have demonstrated that conditional liver-specific β-catenin knockouts, 14,15 inducible liver-specific adenomatous polyposis coli knockouts, 16 and Lrp5/6 knockouts 17 loosen zonation patterns, supporting Wnt/β-catenin as the gatekeeper of liver metabolic zonation. The impact of Wnt/β-catenin–induced metabolic changes on liver carcinogenesis has recently been thoroughly explored 18–20 …”
Section: Spatial Heterogeneity In the Mammalian Livermentioning
confidence: 99%